Ingots Defects under the influence of Solidification and Freezing Conditions. (Baghdad Science Journal, 2025)
The results of research to reach the conditions that prevents the emergence of primary or secondary voids and achieve worker benefit from molded by almost 100%, which was the situation that cast poured in a mold heated and insulated from all sides to achieve freezing directional full starting from the region remote from the casting and ending then. Has also been compared to the microscopic structure of the resulting castings of various molding conditions, as these conditions have achieved the best sound microscopic structures.